(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: The disease caused by Strongyloides stercoralis (S. stercoralis) affects over 600 million people worldwide, primarily transmitted through skin and mucous membranes. Infected individuals often show no typical symptoms but may experience itching, fever, urticaria, abdominal pain, diarrhea, dyspepsia, weight loss, and in severe cases, life-threatening complications in immunocompromised patients, with a mortality rate as high as 85%. Objectives: To determine the prevalence of S. stercoralis antibodies using the ELISA technique and to investigate related factors in patients examined at the Parasitology Clinic, Tay Nguyen’s University Hospital, in 2022. Materials and methods: All patients aged 3 years and older who visited the parasitology clinic at the University of Tay Nguyen Hospital. A cross-sectional study design was employed. Results: The prevalence of S. stercoralis antibodies was 32.0% (CI 95% = 26.3% - 38.1%). Individuals under 18 years old, with an education level below primary school, working in agriculture, frequently going barefoot, regularly coming into contact with soil, and not using protective equipment during farming were found to have a higher likelihood of infection. Conclusion: There is a correlation between S. stercoralis infection rates and factors such as age group, education level, occupation, going barefoot, soil exposure, and use of protective equipment.